PLC based PID control for induction motor drive using VFD (Aintelia Science Notes, 2023)
In today's rapidly developing and changing landscape, PLC technology, widely used in the field of industrial automation, offers users various solutions. In industry, management, and scientific technical jobs, the execution of tasks without human labor is achieved through automation and machines. In this context, Asynchronous motors are preferred over other electrical machines due to their lower cost and being the most widely used machine in the industry. In this study, the control of an Asynchronous motor was realized using a PLC with a VFD driver. In the established experimental system, the speed of the Asynchronous motor was controlled using a Proportional Integral Derivative (PID) controller algorithm. Different control PID values were experimented with constant speed trials to achieve the best results. The obtained results were interpreted through system graphs.